PENGARUH PENYERAPAN TENAGA KERJA DAN INDUSTRALISASI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SIDOARJO - Akbar Kurniawan; Muhammad Yasin (CV. Denasya Smart Publisher, 2024)
This research aims to determine the effect of the number of workers working in large and medium industries and the number of large and medium industries on the rate of economic growth (GRDP) in Sidoarjo Regency. The type and source of data used is a quantitative approach with secondary time series data for the 2011-2021 period. Based on the results of multiple linear regression, the following results were obtained: the adjusted R2 value was 0.947 or 94.7%, and also the F-count had a value of 89.776 > F-table 4.103 and a significance value of 0.000. Meanwhile, the t-count (X1) of 1.608 is smaller than the t-table of 1.796 and a significance value of 0.147 is obtained which is greater than the significance level of 0.05 (0.147 > 0.05). Meanwhile, the t-count of 12.946 is greater than the t-table of 1.796 and a significance value of 0.000 is obtained, which is smaller than the significance value of 0.05.